Upaya Meningkatkan Produk Kualitas Terbaik dengan Metode DMAIC di PT. X - Jefani Nathanael Gunawan; Benedictus Rahardjo (Jurnal Titra, 2020)
This research discusses efforts on how to increase X company best quality product using DMAIC. The company has a production target of 75% for the best quality ceramic tiles, though it was hard to achieve it since the production in 2019 was only 62%. There are eight lines within the production floor and data showed that the largest defect rate of 43.64% has occurred in line seven. By using Pareto chart, we can see which problem needed to be prior solved and it showed that there were twelve types of defects which then being analyzed using fishbone diagram and 5 whys to have a deep root cause analysis. Some comments have been proposed, one of them is related to the elimination of a dusty environment. By adding a dust collector and implement maintenance schedule, it could significantly result in lowering the impact of dust by 52% and engine damage by 46%.